Utilizing Video for Technology Integration Support in Indonesian EFL Classroom: Usages and Obstacles - Muhamad Nova (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2017)
The use of video as a solution in supporting technology integration in EFL teaching and learning process in Indonesia still faces some obstacles in its utilization. Viewing from this issue, this study explored Indonesian EFL teacher’s perceptions on the usages and obstacles in utilizing video in teaching and learning process. Conducting a survey research by distributing questionnaires purposively to 30 EFL teachers, 22 females and 8 males, the results revealed that the Indonesian EFL teachers found that video is very beneficial in teaching and learning process, especially in delivering the learning material, building students’ background knowledge, bringing real-life language context, providing visual and audio input, and serving varieties of language expressions. It also gives positives impacts to students’ learning attitudes, including their interest, motivation, and learning styles. Even though it brings beneficiary effects, many Indonesian EFL teachers also mentioned five obstacles faced in using video in their classroom: limitation of facilities at school, lack of technical support at school, difficulties in finding suitable video, lack of skill in editing video, and less focus students on learning. Reflecting up from these results, it is suggested for EFL teachers to use video in improving the teaching and learning process in the classroom. It is also recommended for the EFL teachers to attend teacher professional development program to enrich their competence and skill in using video in teaching and learning process. Moreover, school principals’ are recommended to support the school facilities to promote technology integration at school.